Continuous GPS measurements of postglacial adjustment in Fennoscandia, 2 : modeling results. - Milne, G. A.; Mitrovica, J. X.; Davis, J. L.; Scherneck, H. G.; Johansson, J. M.; Koivula, H.; Vermeer, M. (Journal of Geophysical Research: Solid Earth, 2004)
Data collected under the auspices of the BIFROST GPS project yield a geographically dense suite of estimates of present-day, three-dimensional (3-D) crustal deformation rates in Fennoscandia [ Johansson et al., 2002 ]. A preliminary forward analysis of these estimates [ Milne et al., 2001 ] has indicated that models of ongoing glacial isostatic adjustment (GIA) in response to the final deglaciation event of the current ice age are able to provide an excellent fit to the observed 3-D velocity field. In this study we revisit our previous GIA analysis by considering a more extensive suite of forward calculations and by performing the first formal joint inversion of the BIFROST rate estimates. To establish insight into the physics of the GIA response in the region, we begin by decomposing a forward prediction into the three contributions associated with the ice, ocean, and rotational forcings. From this analysis we demonstrate that recent advances in postglacial sea level theory, in particular the inclusion of rotational effects and improvements in the treatment of the ocean load in the vicinity of an evolving continental margin, involve peak signals that are larger than the observational uncertainties in the BIFROST network. The forward analysis is completed by presenting predictions for a pair of Fennoscandian ice histories and an extensive suite of viscoelastic Earth models. The former indicates that the BIFROST data set provides a powerful discriminant of such histories. The latter yields bounds on the (assumed constant) upper and lower mantle viscosity (νUM, νLM); specifically, we derive a 95% confidence interval of 5 × 1020 ≤ νUM ≤ 1021 Pa s and 5 × 1021 ≤ νLM ≤ 5 × 1022 Pa s, with some preference for (elastic) lithospheric thickness in excess of 100 km. The main goal of the (Bayesian) inverse analysis is to estimate the radial resolving power of the BIFROST GPS data as a function of depth in the mantle. Assuming a reasonably accurate ice history, we demonstrate that this resolving power varies from ∼200 km near the base of the upper mantle to ∼700 km in the top portion of the lower mantle. We conclude that the BIFROST data are able to resolve structure on radial length scale significantly smaller than a single upper mantle layer. However, these data provide little constraint on viscosity in the bottom half of the mantle. Finally, elements of both the forward and inverse analyses indicate that radial and horizontal velocity estimates provide distinct constraints on mantle viscosity.